Measuring Financial Performance in Infrastructure: An Application to Europe and Central Asia - Ebinger, Jane O. (World Bank, Washington, DC, 2012)
Unintentional implicit subsidies (hidden costs) to public utilities can be considered an illegitimate claim on public resources. This paper examines the role and sources of hidden costs in the energy and water sectors in the Europe and Central Asia (ECA) region. It reviews available data and introduces a model-the Hidden Costs Calculator-that can be used to quantify the burden on governments of infrastructure policy and implementation decisions. This simple-to-apply model provides insight into three key components of hidden costs that affect infrastructure-poor bill collection rates, excessive losses due to inefficient operations or theft from the networks, and tariffs set below cost-recovery rates. The major advantage of this model is that, using existing data, it can provide a single measure for hidden costs that can be easily calculated, tracked, and reported. Therefore it can monitor and benchmark trends across sectors and countries without extensive or costly data collection. The model compares the difference between actual revenues and revenues that could be anticipated in a well-functioning system operating with cost-covering tariffs, bills paid, and losses normative for networks of a certain age and design. The underlying premise is that quantifying the order of magnitude of each component of hidden costs has potential for strengthening infrastructure policy dialogue and influencing decisionmakers who allocate scarce budgetary resources.